The Impact of Trade Barriers on Exports: The Case of Peru, 1992-2002 - Tello, Mario D. (Pontificia Universidad Católica del Perú. CENTRUM, 2008)
This paper proposes a straightforward methodology to assess and estimate the impact of trade barriers on exports from the Peruvian economy. The results of the application of this methodology indicate that most favored nation (MFN) and/or generalized system of preferences (GSP) tariff rates imposed by developed countries on Peruvian exports are relatively low and, conversely, the number of non-tariff barriers (NTBs) and the average number of NTBs per export tariff line are relatively high. This difference produces a higher estimation of the export impact of the NTBs. An implication of these results is that the new wave of regional preferential trade agreements among developed and developing countries (which face a similar trade barrier structure to the Peruvian one) may not have meaningful effects on trade flows unless it is accompanied by substantial reductions in the number of NTBs per export tariff line.
Keywords: Generalized Systems of Preferences (GSP); Gravity Equation; Most Favored Nation (MFN); Non Tariff Barriers (NTBs); Tariffs; https://purl.org/pe-repo/ocde/ford#5.02.04